The Quality of Quail Meat Block on Difference Material and Level Binding - Agus Susilo; Eny Sri Widyastuti; Yany Esti Nurvikawati (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2011)
The objective of this research was to find out the difference quality of quail meat block using STPP, sodium alginate and carrageenan of texture and chemical properties. The materials of the research were quail meat block from rejected quail’s breast, STPP, sodium alginate and carrageenan.  The method of this research was nested experiment using randomized block design.  The first factors were the kind of binder substance, namely STPP (S), sodium alginate (A) and carrageenan (K).  The second factor was the concentration of each kind of binder, namely 0.25%, 0.37% and 0.5%, respectively.  The variables measured were gel strength, elasticity and chemical properties (pH, WHC, protein content). The results showed that the use binder substance, namely STPP, sodium alginate and carrageenan gave a highly significant different (P<0.01) on pH and gave no significant different (P<0.05) on WHC, protein content.  Concentration of each kind of binder gave a highly significant different (P<0.01) on WHC and gave no significant different (P<0.05) on pH, protein content, gel strength and elasticity.  The highest pH value and WHC was on using STPP 0.5%, whereas the highest protein content value gel strength, elasticity was on using sodium alginate 0.5%. The conclusion of this research that the increasing of STPP, sodium alginate and carrageenan gave no significant different to meat block quality. The highest texture value as quality determiner was the increasing of sodium alginate 0.5%.   Keywords : Quail meat block, STPP, sodium alginate, carrageenan